Profil Berpikir Kritis IPA Siswa Kelas VIII SMP Negeri di Kota Ende Berdasarkan Prespektif Gender - Harso, Aloisius; Gago, Jumilah (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2018)
The aims of this research is was to find out the profile of overall science critical thinking ability and based on the gender of viii grade students of SMPN at Ende city. This research was a descriptive research. The population of this research were all the VIII grade students of SMPN at Ende city academic year 2017/2018. As many as 804 students and the sample were 10% of the populations, they were 80 students. This research used random sampling technique. The data were obtained from the score of science critical thinking ability. The data were analyzed by using descriptive analysis. the result shows that the average of science critical thinking ability of students was 66,84 which is categorized as medium or critical enough. Meanwhile, based on the gender perspective, the female group obtained the average as 68,56 which is categorized as high or critical. Meanwhile, male obtained the 62,03 which is categorized as medium or critical enough.